Are firms paying more for performance?. Issue 2 (3rd May 2016) - Forth, John; Bryson, Alex; Stokes, Lucy
Abstract : Purpose: – The purpose of this paper is to investigate changes in the economic importance of performance-related-pay (PRP) in Britain through the 2000s using firm-level data. Design/methodology/approach: – The authors utilise nationally representative, monthly data on the total wage bill and employment of around 8, 500 firms. Using these data, the authors decompose the share of the total economy-wide wage bill accounted for by bonuses into the shares of employment in the PRP and non-PRP sectors, the ratio of base pay between the two sectors, and the gearing of bonus payments to base pay within the PRP sector. Findings: – The growth in the economic importance of bonuses in Britain in the mid-2000s – and subsequent fluctuations since the onset of recession in 2008 – can be almost entirely explained by changes in the gearing of bonus to base pay within the PRP sector. There has been no substantial change in the percentage of employment accounted for by PRP firms; if anything it has fallen over time. Furthermore, movements in the gearing of bonuses to base pay in the economy are heavily influenced by changes in Finance: a sector which accounts for a large proportion of all bonus payments in Britain. Research limitations/implications: – The paper demonstrates the importance of understanding further how firms decide the size of bonus payments in a given period. Originality/value: – This is the first paper to present monthly firm-level data for Britain on the incidence and size of bonus payments in the 2000s.